0 - Editorial - Murunga, Godwin; Fuh, Divine (CODESRIA Bulletin, 2021)
The theme for this edition of the CODESRIA Bulletin is curled from the thematic priorities of the 2017-2021 Strategic Plan. These are: ‘Democratic processes, governance, citizenship and security in Africa’ and ‘Ecologies, Economies and Societies in Africa.’ The Bulletin addresses two important sets of questions. The first focuses on how Africa, along with all the changes and transformations that define it today, is and should be governed. That includes issues of statehood, democratization, the rule of law and human rights, security and violence, transitional justice, and other attendant governance processes and mechanisms at local, national, regional and international levels. These continue to constitute some of the most important issues of concern in many African countries that, naturally, also orient the work of the Council. The second explores aspects of the Anthropocene in Africa, the forms it takes, its histories and trajectories and impact on a broad set of sectors including the continent’s burgeoning economies. This theme provokes important questions related to land, food security and poverty that persistently dominate public debate and remain of global concern. Africa continues to be challenged by the contradictions and complexities of ‘development’, climate change and population growth, especially in cities. The evolving nature of rural and urban centres, particularly propelled by the growing purchasing power of new elites, coupled with the expanding wealth gap are redefining and creating new dynamics for cohabitation. Insecurity, uncertainty and undignified living constitute key challenges for a continent that continues to struggle with the global capitalist system. Lionel Zevounou starts with a critique of what he considers an exclusionary interdisciplinarity, as he argues that law is marginalised in Africa, and specifically CODESRIA’s postcolonial critiques of thought systems and knowledge production. Munamato Chemhuru then continues with the debate begun in the previous issue of the bulletin on the contextual relevance of democracy in Africa, as he argues for a shift to adopting democratic governance frameworks grounded in African existential realities. Leah Junck examines community activism and organizing around neighborhood security on examples from South Africa while Sean Maliehe tackles the continent’s relationship with human economy building on the case of mobile money in South Africa to explore people’s entrepreneurial encounters with changing capital. Theresa Moyo critically examines the benefits from and equitable distribution of wealth from extractive industries, outlining how a different future can be realised from Africa’s mineral wealth. Raphael Mulaha Kweyu’s piece addresses climate change and resilience strategies by marginalised communities in Kenya, specifically addressing issues related to governance. Kellen Kiambiati and Anne Kariuki’s contribution discusses strategies to deal with corruption through values based approaches that take on board local epistemologies while Edrine Wanyama, in the last piece in this collection, highlights the importance of variable geometry in enhancing economic growth in East Africa. The last group of contributions from Rokhaya Fall, Abdoullah CISSE, Kofi Anyidoho, Chambi Chachage, Biodun Jeyifo and Yusuf Bangura pay homage to colleagues who moved on in 2017. Over the period covered by this issue of the CODESRIA Bulletin, we learned with devastation of the sudden and shocking death of colleagues whose prominent role in the affairs of the Council has been notable. Within the space of a few months in 2017, the CODESRIA community lost four colleagues: Aminata Diaw Cissé (died April 14 2017), Abubakar Momoh (died 29 May 2017), Francis Abiola Irele (died July 2 2017) and Abdul Raufu Mustapha (died 8 August 2017). In this issue of the Bulletin, we appreciate their contribution to wider struggles, celebrate their tenacity and combativeness and take note of their indelible contribution to the Panafrican knowledge project. Aminata Diaw was a laureate of CODESRIA’s first Democratic Governance Institute in 1992 before she moved to build a university career as a feminist and philosopher in the Department of Philosophy at the University of Cheikh Anta Diop. Before her passing on, she served CODESRIA from 2010-2016 as Head of the Training, Grants and Fellowships (TGF) Programme. It is an interesting coincidence that Abubakar Momoh was also a laureate of the Democratic Governance Institute of 1996. As the CODESRIA tribute to Abdul Raufu Mustapha points out, he too was involved in the Democratic Governance Institute, having served as its Director in 2002. He later served as a member of the Scientific Committee (2009-2011) and, just before his death, was a member of the Internal Review Committee on CODESRIA’s Intellectual Agenda. Abiola Irele, even though not a regular participant in CODESRIA activities, was strikingly present through his work on ‘Negritude’ and Africa’s intellectual response to the colonial condition, which formed a core part of the ideological foundations of the Council’s mission. Thus, even though these intellectual giants have passed on, their intellectual contributions borne out of various intersections in the thought spaces provided by CODESRIA invite our honour through a critical engagement with their ideas. As we honour the departed, the Council also welcomes the appointment a new Executive Secretary at the helm of the Council. On the 1st of June, Dr. Godwin Murunga, formerly at the Institute for Development Studies, University Nairobi and African Leadership Centre took over from Dr. Ebrima Sall as the 7th Executive Secretary of CODESRIA. This appointment is the sixth successful transition at the Council in its 44-year history. Godwin Murunga is also an alumni of the CODESRIA Democratic Governance Institute 1997, before going on to serve as one of the Council’s youngest Executive Committee members from 2005 to 2011. His tenure thus represents a remarkable generational shift and transition. The agenda for the new leadership at the Council is properly framed in the note Prof. Dzodzi Tsikata, President of CODESRIA shared announcing the appointment of Dr. Godwin Murunga. Locating the agenda in the ongoing CODESRIA internal review process, the note focuses on reviewing and reforming systems, processes, and engagements with its constituencies and stakeholders, particularly policy communities. This agenda is one that should revitalise Council programming and find new ways of engaging the broader community that benefits from CODESRIA’s work.